STRATEGI PENILAIAN AUTENTIK KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI (STUDI KASUS DI SMP NEGERI 1 PABUARAN KABUPATEN CIREBON) - Halimi Ansor (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2018)
This study aims to describe the strategy of planning, implementing and evaluating the results of an authentic assessment of the 2013 curriculum for PAI (Islamic Studies) subjects and budi pekerti (ethics and character). This type of research is qualitative research. The subjects of the study were VII grade PAI teachers, grade VII guardians and Counseling Guidance teachers. Data collection through observation, interview, documentation study, and triangulation. Data analysis uses data reduction, data display, and conclusion drawing. The results of the study show: Planning an authentic assessment of the 2013 curriculum for PAI and Budi Pekerti subjects is still not optimal. Teachers of PAI subjects do not compile the midterm and daily assessment scores and do not plan portfolio assessments. The application of an authentic assessment of the 2013 PAI curriculum and Budi Pekerti has not run optimally. PAI subject teachers do not use observation sheets or journals and do not apply self-assessment, peer assessment, project appraisal, and portfolio assessment. Authentic assessment of the 2013 PAI and Budi Pekerti curriculum for 280 students. Assessment of attitudes for 27 students obtaining the category